The Chinese automobile industry and government policy. (December 2020) - Chen, Yuan; Lin Lawell, C.-Y. Cynthia; Wang, Yunshi
Abstract: China is experiencing rapid economic growth and, along with it, rapid growth in vehicle ownership. The rapid growth in vehicle ownership and vehicle usage is linked to increasing global warming, emissions, air pollution, and other problems. In this paper, we discuss the Chinese automobile industry and government policy, and review the literature on vehicle markets and policy in China. Using a comprehensive annual data set we have collected and constructed of all the car models marketed from the year 2004 to year 2013 in the Chinese automobile industry, we then discuss and describe the characteristics of vehicles in the Chinese automobile industry. The detailed information, description, research, and data presented in this paper have important implications for those in industry, government, society, academia, and non-governmental organizations interested in the Chinese automobile market, the automobile industry, and transportation policy.